Anti-tuberculosis Drug-induced Hepatitis - Karim, ASM Bazlul; Musabbir, Nadira (Bangladesh Journal of Child Health, 2023)
Among the first line anti-TB drugs, INH, Rifampicin and Pyrazinamide are considered to be the most hepatotoxic drugs and cause drug induced hepatitis. Pyrazinamide causes both dose-dependent and idiosyncratic hepatitis whereas Isoniazid and Rifampicin induced hepatotoxicity are considered to be idiosyncratic. There are several risk factors for hepatotoxicity such as old age, malnutrition, genetic predisposition, HIV infection as well as chronic Hepatitis B and C infections. Anti-TB drug induced hepatitis usually occurs within 2 months after starting treatment. Patient may present with mild symptoms to severe acute hepatitis or even acute liver failure. Various guidelines have been published regarding the management of ATT and restarting anti TB drugs. This article reviews the incidence, risk factors, mechanism, diagnosis and management strategies of anti-TB drug induced hepatitis. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 23-27